Pemanfaatan Media Televisi dalam Memenuhi Kebutuhan Informasi Masyarakat Desa Sungai Ruan Ilir Kabupaten Batang Hari - Dwi Purniati; Samsu; Adi Iqbal (Journal of Religion and Film, 2022)
This research is motivated by problems with the existence of obstacles that make people use Jambi TV media in their need for information. The objectives to be achieved in this study are to find out the utilization of Jambi TV television media, and the effects of information from Jambi TV television media and the constraints of society in utilizing Jambi TV television. The results of this study indicate that the use of television media for the people of Sungai Ruan Ilir village, Maro Sebo Ulu sub-district (Studi Jambi TV) is the use of television media to meet community needs so that the information the community wants is fulfilled and they don't have to wait long to get information. The people of Sungai Ruan Ilir Village chose Jambi TV Television media by getting information that was very easy to understand, understood by the community. while the effect of information from the Jambi TV television media for the community returns to the community itself, if they respond to the information they get by thinking negatively then it is bad for them while they respond to information by thinking positively it is good for them and very useful. The Jambi TV television media cannot always use it to obtain information because there are problems for the community in utilizing Jambi TV, such as when the network is lost and when there is a power outage, the community cannot take advantage of Jambi TV television media.